Comparing Nanohydroxyapatite Graft and Other Bone Grafts in the Repair of Periodontal Infrabony Lesions: A Systematic Review and Meta-Analysis - Muhammad Saad Shaikh (MDPI AG, 2021)
Objective: To compare the results of periodontal infrabony lesions treated using nanohydroxyapatite (NcHA) graft with other bone grafts (BGs). Methods: Four electronic databases were searched including PubMed (NLM), Embase (Ovid), Medline, and Dentistry and Oral Sciences (EBSCO). The inclusion criteria included randomised controlled clinical trials (RCTs) and controlled clinical trials (CCTs). The clinical results of NcHA were compared with other BGs. For clinical attachment level (CAL) gain, probing pocket depth (PPD) decrease, and gingival recession (REC) change, weighted averages and forest plots were computed. Results: Seven RCTs fulfilled the selection criteria that were included. When NcHA was compared to other BGs, no clinically significant differences were found in terms of each outcome assessed, except the REC change for synthetic BGs as compared to NcHA. Conclusions: The use of an NcHA graft showed equivalent results compared to other types of BGs. To further validate these findings, future studies are required to compare the NcHA and various BGs over longer time periods and in furcation deficiencies.